Estabelecimentos canavieiros típicos da microrregião do Brejo Paraibano, na Paraíba - Ribon, Miguel; Paniago, Euter; Fernandes de Araújo, José Geraldo; Taranto Fortes, Nicolino (Revista Ceres, 2025)
This study tries to identify characteristics of Sugar cane producers, mainly the small and medium ones. Data were collected in a region of the State of Paraiba, in 1984.